Integrated worksheets as an innovative learning media to increase basic nursing competency in ners professional students - Nur Aini; Erma Wahyu Mashfufah (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2018)
ABSTRACT Introduction : One of the learning methods in the professional practice of professional basic nursing department (KDP) nurses is pre and post conference, where students must make a preliminary report (LP) and master the material. The problem that occurs and complained by the supervisor is that students only write reports without understanding the contents so that when their cognitive abilities are lacking in guidance. Therefore, the researchers made innovations to make worksheets as innovative learning media to improve basic nursing competencies in professional student students. Method : Research design was classroom action research (CAR). consists of 4 stages, that were: 1). Planning, preparation of worksheets. 2) Implementation, the application of worksheets, 3). Observation, observe the results of the application of worksheets on student abilities 4). Reflection, reflecting on the results of observation and discussion. The study was conducted on 37 professional students in Ners practice in March - October 2018. Result : The majority of students agree with the use of worksheets, and the percentage of graduation  of the final exam is 84%. Discussion: Worksheets make it easier for students to understand basic nursing material, because students must work on the questions so that they make their understanding better. The application of worksheets needs to be applied to other subjects, as well as the need to try other learning models or methods in professional practice, so that student competencies increase. Keywords : ners student, basic nursing, worksheet, classroom action research. ABSTRACT Latar Belakang : Salah satu metode pembelajaran dalam praktik profesi ners departemen keperawatan dasar profesi (KDP) adalah pre dan post conference, dimana mahasiswa harus membuat laporan pendahuluan (LP) dan menguasai materi tersebut. Permasalahan yang terjadi dan dikeluhkan oleh pembimbing adalah mahasiswa hanya sekedar menulis laporan tanpa memahami isinya sehingga saat bimbingan kemampuan kognitif mereka kurang. Oleh karena itu, peneliti membuat inovasi membuat Worksheets sebagai media pembelajaran inovatif untuk meningkatkan kompetensi keperawatan dasar pada mahasiswa profesi ners. Metode : Jenis penelitian adalah penelitian tindak kelas atau CAR (classroom action research). terdiri dari 4 tahapan yaitu : 1). Perencanaan, dilakukan penyusunan worksheet. 2) Pelaksanaan, yaitu penerapan worksheet, 3). Pengamatan, mengamati hasil penerapan worksheet terhadap kemampuan mahasiswa 4). Refleksi, merefleksi diri berdasarkan hasil observasi dan diskusi. Penelitian dilakukan pada mahasiswa praktik profesi Ners sejumlah 37 mahasiswa pada bulan Maret - Oktober 2018. Hasil : Mayoritas mahasiswa setuju dengan penggunaan worksheet, dan prosentase hasil kelulusan ujian final exam sebesar 84%. Diskusi : Worksheet membuat mahasiswa lebih mudah memahami materi keperawatan dasar, karena mahasiswa harus mengerjakan soal-soal sehingga membuat pemahaman mereka lebih baik. Penerapan worksheet perlu dicoba diterapkan pada mata kuliah lain, serta perlu dicoba model atau metode pembelajaran yang lain dalam praktik profesi ners, sehingga kompetensi mahasiswa meningkat. Keywords: profesi ners, keperawatan dasar, worksheet, classroom action research.